فاعلية التعليم الإلكتروني في ظل إنتشار فيروس كورونا من وجهة نظر المدرسين بكلية العلوم الإنسانية والإجتماعية بجامعة محمد بوضياف المسيلة. - بلعباس, عبد الحميد; بوحيلة, رضوان (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة إلى الكشف عن فاعلية التعليم الإلكتروني في ظل إنتشار فيروس كورونا من وجهة نظر المدرسين في كلية العلوم الإنسانية والإجتماعية بجامعة محمد بوضياف بالمسيلة، ولتحقيق أهداف هذه الدراسة تم الإعتماد على المنهج الوصفي التحليلي، وتكونت عينة الدراسة من (50) عضو هيئة تدريس في كلية العلوم الإنسانية والإجتماعية بجامعة محمد بوضياف بالمسيلة ممن قاموا بالتدريس خلال فترة إنتشار فايروس كورونا من خلال نظام التعليم الإلكتروني، وجرى جمع البيانات اللازمة باستخدام إستبيان بلغ معامل ثباته (0.804) بعد تطبيقه على عينة الدراسة. كشفت الدراسة أن تقييم عينة الدراسة لفاعلية التعليم الإلكتروني في ظل انتشار فيروس كورونا من وجهة نظرهم كان متوسطاً، وجاء تقييمهم لمجال إستمرارية التعليم الإلكتروني ومجال معيقات إستخدام التعليم الإلكتروني ومجال تفاعل أعضاء هيئة التدريس مع التعليم الإلكتروني، ومجال تفاعل الطلبة في إستخدام التعليم الإلكتروني متوسطاً، وأوصى الباحثون بعقد دورات تدريبية في مجال التعليم الإلكتروني لكل من المدرسين والطلبة والمساعدة في التخلص من كافة المعيقات التي تحول دون الإستفادة من نظام التعليم الإلكتروني المتبع، وضرورة المزاوجة بين التعليم المواجهي والتعليم الإلكتروني في مؤسسات التعليم العالي مستقبلا. This study aimed to reveal the effectiveness of e-learning in the light of the spread of the Coronavirus from Faculty of Humanities and Social Sciences at the University of Muhammad Boudiaf – M'sila. To achieve the goals of the study descriptive analytical approach was used, The study sample consisted of (50) instructors from Faculty of Human and Social Sciences, of M'sila University who taught during the spread of Coronavirus using the e-learning syste m. Data were collected through a questionnaire which its reliability reached to (0.804) and applied on the study sample. The results revealed that the effectiveness of e-learning in the light of the spread of the Coronavirus from the study sample perspective was medium, the evaluation of the continuity of e-learning, its obstacles, the interaction of instructors with e-learning and the interaction of students with e-learning in light of the spread of the Coronavirus was medium. The researchers recommended conducting training courses in the field of e-learning for both instructors and students, help get rid of all the obstacles that prevent utilizing from the e-learning system, and combine face-to-face and e-learning in higher education institutions in the future.
The Effectiveness of e-learning in light of the spread of the “ Coronavirus from the point of view of teachers at the faculty of Humanities and Social Sciences in The university of Muhammad Boudiaf - M'sila.
مقال
Keywords: جائحة 2019 ، جامعة المسيلة ، الفاعلية ، التعليم عن بعد ، الكلية; Pandemic 2019, University of M’sila , Effectiveness, Distance Learning, faculty.